2004
DOI: 10.1103/physreve.69.066607
|View full text |Cite
|
Sign up to set email alerts
|

Properties of one-dimensional photonic crystals containing single-negative materials

Abstract: The transmission properties of a one-dimensional photonic crystal containing two kinds of single-negative (permittivity- or permeability-negative) media are studied theoretically. We show that this structure can possess a type of photonic gap with zero effective phase (phi(eff) ). The zero-phi(eff) gap distinguishes itself from a Bragg gap in that it is invariant with a change of scale length and is insensitive to thickness fluctuation. In contrast to a photonic gap corresponding to zero averaged refractive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(116 citation statements)
references
References 21 publications
0
115
0
1
Order By: Relevance
“…It is straightforward to ask if similar physics can happen in optical systems composed by opaque materials, such as epsilon-negative (ENG) media and munegative (MNG) media. In 2004, Jiang et al [61] considered a 1D PC formed by alternative stacking of ENG layers (with ε 1 < 0, μ 1 > 0, thickness d 1 ) and MNG layers (with ε 2 > 0, μ 2 < 0, thickness d 2 ). Based on the same mathematics, they found that the dispersion relation of the system is determined by η η κ η η…”
Section: Zero-phase ( φ Eff ) Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…It is straightforward to ask if similar physics can happen in optical systems composed by opaque materials, such as epsilon-negative (ENG) media and munegative (MNG) media. In 2004, Jiang et al [61] considered a 1D PC formed by alternative stacking of ENG layers (with ε 1 < 0, μ 1 > 0, thickness d 1 ) and MNG layers (with ε 2 > 0, μ 2 < 0, thickness d 2 ). Based on the same mathematics, they found that the dispersion relation of the system is determined by η η κ η η…”
Section: Zero-phase ( φ Eff ) Gapmentioning
confidence: 99%
“…This discovery motivated people to ask the inverse questionunder what condition should such system exhibit a PBG ? Jiang et al [61] noticed that, when the effective phase accumulation (not the real phase since waves inside each layer are evanescent) across the unit cell is exactly zero, i.e.,…”
Section: Zero-phase ( φ Eff ) Gapmentioning
confidence: 99%
“…It was shown that a one-dimensional photonic crystal (1DPC) composed of alternating slabs of ordinary double-positive (DPS) and DNG media can have a type of photonic bandgap (PBG) corresponding to zero averaged refractive index (n) [9][10][11][12]. Moreover, it is well known that a 1DPC constituted by a periodic repetition of MNG and ENG layers can possess another type of photonic gap with effective phase (ϕ eff ) of zero [13][14][15]. When the periodicity of photonic crystal structure is broken, wave propagation is not described by Bloch states.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the left hand side of Eq. (10), the effective phase or the Bloch phase is defined as φ eff = KΛ [29]. In general, K is complex, i.e., K = K r − jK i .…”
Section: Basic Equationsmentioning
confidence: 99%